Information and communication technology-based interventions to support healthcare in migrants. (13th November 2019) - Vaccaro, F G; Alecreu, A Oradini; Scardoni, A; Frascella, B; Vigezzi, G P; Odone, A; Signorelli, C
Abstract: Background: Advances in the field of Information and Communication Technology (ICT) are revolutionizing healthcare, while massive migration flows and cross-border populations' transit impose the planning, implementation, and evaluation of new integrated healthcare services and programmes. Nevertheless, no conclusive evidence exists on the vast potential offered by ICT to promote healthcare in migrant populations. Methods: We carried out a systematic review following the Preferred Reporting Items for Systematic Reviews and Meta-Analysis guidelines to retrieve, pool and critically appraise all the available evidence on the effectiveness of ICT-based interventions to support the healthcare provision to migrant and in-transit populations in Europe. We searched the electronic databases Medline and Embase, relevant grey literature and consulted with experts in the field. We restricted the area of interest to EU/EEA countries and included studies providing original quantitative data. Results: Out of 127 retrieved records, 53 (42%) met the inclusion criteria. Included studies were classified in the following four interventions: implementation of healthcare services (47%), patients' education (26%), healthcare services' monitoring (17%), and interventions on providers (10%). The most relevant data refer to telemedicine, prevention interventions, and healthcare data sharing and the most represented specific health-topic is that of mental health (26%). We present available data qualitatively and quantitatively pooled by country, type of ICT, target population and health topic. Conclusions: Selected ICT-based interventions have been implemented in Europe to promote healthcare in migrant populations; however, in most cases, no monitoring and evaluation exist on their impact, effectiveness, and cost-effectiveness. Strengthened efforts are needed to identify, plan, implement and evaluate effective interventions and share best practices to protect in-transit populations' health. Key messages: Information and Communication Technology (ICT) offer great potential to promote health-care in migrant populations. Effective ICT interventions and best practices should be shared across Europe.